Akad Nikah Online dalam Perspektif Keputusan Ijtima’ Ulama Komisi Fatwa MUI Se-Indonesia VII Tahun 2021 dan Peraturan menteri agama No 20 Tahun 2019 tentang Pencatatan Pernikahan - Nur Sultan Al Khuluqi Sirait; Akmaluddin Syahputra (Dinasti Review Publisher, 2024)
This article is a literature study carried out by collecting all the literature that discusses online marriage contracts in Islam. Analyze and identify marriage registration, and formulate recommendations for creating new, more optimal arrangements. The results of this study show that there needs to be consideration in making regulations regarding the registration of marriages whose contracts are carried out online by reviewing the Ijtima' Ulama Decree of the Indonesian MUI Fatwa Commission VII of 2021 and Regulation Of Menteri Agama No. 20 of 2019 concerning Marriage Registration. Then there is a need for further research regarding the marriage registration process to increase public trust in online marriage contracts. It is hoped that this research can help the government in making regulations regarding online marriage registration in Indonesia. Apart from that, it is also hoped that this study will become a reference for future researchers who discuss the issue of online marriage contracts in more depth